Validating a Scale for Innovation in Sustainable Water Management in the Manufacturing Sector: A Slovenian Study - Moretti, Melita (Naše gospodarstvo/Our economy, 2023)
Based on the results of our research, we have developed a reliable and valid scale for assessing the innovation success of sustainable development practices, with a specific focus on reducing drinking water consumption in the production sector, where so-called industrial water is used (for production, cooling, or both). We found that the assessment of innovation success in sustainable development management practices, specifically aimed at reducing drinking water consumption in the production sector, comprises two dimensions: measuring success in water use innovations and innovative success in water treatment and conservation. The study also found that the assessment of innovation success in sustainable development management practices, particularly focused on reducing drinking water consumption in the production sector, is influenced by reporting on sustainable water management, innovations in organizational systems, innovations in materials and processes for sustainable water use, and analysis with goal setting in water use innovations. This comprehensive analysis provides organizations without established metrics with a tool to identify potential areas for improvement, thereby enhancing ecological methods and increasing production efficiency.